Assessing Public Health and Social Measures Against COVID-19 in Japan From March to June 2021 - Hayashi, Katsuma; Kayano, Taishi; Anzai, Asami; Fujimoto, Marie; Linton, Natalie; Sasanami, Misaki; Suzuki, Ayako; Kobayashi, Tetsuro; Otani, Kanako; Yamauchi, Masato; Suzuki, Motoi; Nishiura, Hiroshi (Frontiers in Medicine, 2022)
Background: Public health and social measures (PHSM) against COVID-19 in Japan involve requesting the public to voluntarily reduce social contact; these measures are not legally binding. The effectiveness of such PHSM has been questioned with emergence of the SARS-CoV-2 Alpha variant (B.1.1.7), which exhibited elevated transmissibility. Methods: We investigated the epidemic dynamics during the fourth epidemic wave in Japan from March to June 2021 involving pre-emergency measures and declaration of a state of emergency (SoE). We estimated the effective reproduction number (Rt) before and after these interventions, and then analyzed the relationship between lower Rt values and each PHSM. Results: With implementation of pre-emergency measures (PEM) in 16 prefectures, the Rt was estimated to be <1 in six prefectures; its average relative reduction ranged from 2% to 19%. During the SoE, 8 of 10 prefectures had an estimated Rt <1, and the average relative reduction was 26%–39%. No single intervention was identified that uniquely resulted in an Rt value <1. Conclusion: An SoE can substantially reduce the Rt and may be required to curb a surge in cases caused by future SARS-CoV-2 variants of concern with elevated transmissibility. More customized interventions did not reduce the Rt value to <1 in this study, but that may be partly attributable to the greater transmissibility of the Alpha variant.